2010
DOI: 10.1117/1.3446896
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes for next generation very large scale integration interconnects

Abstract: Abstract. We investigated the application of one-dimensional fluid model in modeling of electron transport in carbon nanotubes and equivalent circuits for interconnections and compared the performances with the currently used copper interconnects in very-large-scale integration (VLSI) circuits. In this model, electron transport in carbon nanotubes is regarded as quasi one-dimensional fluid with strong electron-electron interaction. Verilog-AMS in Cadence/Spectre was used in simulation studies. Carbon nanotubes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 83 publications
(144 reference statements)
0
54
0
Order By: Relevance
“…Most of them explores chemical vapor deposition technologies and successful fabrication experience on CNT includes [8], [9], [10], [11], [12], [13]. It has been shown that bundled SWCNTs can outperform copper interconnects in signal wave transportation along a long global interconnect [7], [14], [15], [16], [17]. For example, it is shown in [7] that the resistance of bundled SWCNTs can be achieved 50% smaller compared to that of copper at the same size of a long interconnect at 22nm technology node.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them explores chemical vapor deposition technologies and successful fabrication experience on CNT includes [8], [9], [10], [11], [12], [13]. It has been shown that bundled SWCNTs can outperform copper interconnects in signal wave transportation along a long global interconnect [7], [14], [15], [16], [17]. For example, it is shown in [7] that the resistance of bundled SWCNTs can be achieved 50% smaller compared to that of copper at the same size of a long interconnect at 22nm technology node.…”
Section: Introductionmentioning
confidence: 99%
“…Due to high electro-thermal conductivities of different variants of carbon nanotube (CNT) and graphene, research has advanced further to explore potential of these nano-materials as future VLSI interconnect [1][2][3][4][5][6] and sensors [7,8]. Because of high thermal conductivity, CNT interconnects can quickly drain out heat energy to make interconnect more thermally stable [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Considering all these benefits metallic single-wall carbon nanotube (SWCNT) and multiwall carbon nanotube (MWCNT) have been studied intensely as a future VLSI interconnects material [10][11][12][13][14][15]. It is now a common trend to study the performances of interconnects made of all the variants of CNT and their bundles [3,[13][14][15]. Most of these previous works focused on electronic transport rather than giving focus to thermal transport, thermal instability induced performance degradation and ultimately thermal breakdown of interconnect.…”
Section: Introductionmentioning
confidence: 99%
“…Beside high electro-thermal conductivities, nanometer feature size made these materials the perfect candidates to embed into shrinking devices. Since the discovery of carbon nanotubes researchers proposed various applications of this material ranging from device designing to sensor applications [3][4][5][7][8][9][10][11] . It has been found that CNTs have very interesting temperature dependent resistivity which can be exploited in designing temperatures sensors 12,13 .…”
Section: Introductionmentioning
confidence: 99%